Direct methods for the approximate solution of operator equations with nonzero kernel - Malyshev К. I.; Tikhonenko, N. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We justify direct methods for the approximate solution of linear operator equations with nonzero kernels and apply these methods to the justification of projective methods for the approximate solution of standard singular integral equations with Cauchy kernels and positive index on the unit disk.